Canine Adipose-Derived Mesenchymal Stromal Cells Reduce Cell Viability and Migration of Metastatic Canine Oral Melanoma Cell Lines In Vitro - Teng, Fwu Shing [UNESP]; de Faria Lainetti, Patricia [UNESP]; Simão Franzoni, Mayara [UNESP]; Fernando Leis Filho, Antonio [UNESP]; de Oliveira Massoco Salles Gomes, Cristina; Laufer-Amorim, Renée [UNESP]; Martins Amorim, Rogério [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (MDPI, 2024)
Canine oral melanoma (COM) is a promising target for immunomodulatory therapies aimed at enhancing the immune system’s antitumor response. Given that adipose-derived mesenchymal stem cells (Ad-MSCs) possess immunomodulatory properties through cytokine release, we hypothesized that co-culturing Ad-MSCs and canine peripheral blood mononuclear cells (PBMCs) could stimulate interleukin (IL) production against melanoma cell lines (MCCLs) and help identify therapeutic targets. This study evaluated IL-2, IL-8, and IL-12 expressions in co-culture with MCCL, Ad-MSCs, and PBMCs and assessed the relationship between gene expression, cell viability, and migration. Using four experimental groups in a Transwell insert system to separate cell types, we found that Ad-MSCs can reduce MCCL migration and viability, though the effect may vary depending on each cell line’s susceptibility. Furthermore, Ad-MSCs modified IL expression profiles in co-cultured cells. Our findings suggest that Ad-MSCs could have therapeutic potential for COM by inhibiting cell migration and reducing viability. However, deeper insights into Ad-MSC interactions with the tumor microenvironment and melanoma-specific factors will be essential to optimize therapeutic efficacy.
Keywords: dog; interleukins; melanocyte; peripheral mononuclear cells; stem cells